Investigation of heat exchange in a blown dense layer of granular materials - Solodka, Antonina; Volgusheva, Natalya; Boshkova, Irina; Titlov, Alexandr; Rozhentsev, Andrey (Eastern-European Journal of Enterprise Technologies, 2017)
Experimental studies of heat exchange between a dense layer of granular material and a stream of heated air have been carried out. As a granular material, claydite and gravel were used in a moving and a stationary layer. Temperature curves were obtained for the air flow and the solid component at the inlet and outlet of the installation. The shape of the curves indicates presence of two distinct zones with different heating rates. It was stated that it is expedient to set the heating period in the heat accumulators with a stationary bed within the first period which is characterized by a high heating rate. When calculating duration of the heating period, it is rational to take the value of the final material temperature 10‒15 % lower than the temperature of the heating air at the inlet. It was established that the coefficient of intercomponent heat exchange depends on the gas velocity, the velocity of the bed motion, the gas temperature at the input to the installation and the process duration. It was found that the curves of the dependence of the coefficients of intercomponent heat exchange on the process duration are described by a sigma function. Intensity of heat transfer for a moving layer in the investigated region was commensurable or somewhat higher than that for a stationary layer. It was shown that claydite is the preferred material for a granular packing. The time to onset of a stationary mode for a moving claydite layer was reduced by 2.4 times in comparison with gravel layer and by 2.2 times for a stationary layer.